2015
DOI: 10.1136/bmjopen-2015-008590
|View full text |Cite
|
Sign up to set email alerts
|

Association between sleeping hours and cardiometabolic risk factors for metabolic syndrome in a Saudi Arabian population

Abstract: ObjectivesEpidemiological and molecular studies have shown that sleep duration is associated with metabolic syndrome (MtS), a disease that is on the rise in the Kingdom of Saudi Arabia. We aim to investigate the association between sleep duration and selected cardiometabolic risk factors of MtS in a Saudi Arabian population.SettingSecondary care was given to the participants. There were 2 participating centres, shopping malls in North and South Jeddah, Saudi Arabia.ParticipantsWe recruited 2686 participants ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…However, our results are in concurrence with Arora’s community study, which found that long SDN was linked to a higher risk of metabolic changes, and that chances of elevated triglycerides and central obesity were significantly higher in long sleepers 27. Brocato et al also established that SDN >8 h was associated with cardiometabolic risk factors, namely hypertension, hyperglycemia, and obesity 28. On the other hand, chronic sleep loss was also shown to be a risk factor for the development of weight gain and DM type 2 29.…”
Section: Discussionsupporting
confidence: 92%
“…However, our results are in concurrence with Arora’s community study, which found that long SDN was linked to a higher risk of metabolic changes, and that chances of elevated triglycerides and central obesity were significantly higher in long sleepers 27. Brocato et al also established that SDN >8 h was associated with cardiometabolic risk factors, namely hypertension, hyperglycemia, and obesity 28. On the other hand, chronic sleep loss was also shown to be a risk factor for the development of weight gain and DM type 2 29.…”
Section: Discussionsupporting
confidence: 92%
“…34 Despite these observations, the exact mechanism and causality remain unclear, and some authors have suggested that insulin resistance and sarcopenia share a common cause. 4 Rasmussen et al proposed that resistance to insulin contributed to a decline in the synthesis of skeletal mass protein and resulted in sarcopenia in older people.…”
Section: Discussionmentioning
confidence: 99%
“…For the sleep quality, both long and short sleep durations have been previously reported to be associated with increased HbA1c levels [13,14]. Sleep during the night-time is important for the metabolic process, which has been shown to facilitate blood glucose regulation that is essential for diabetes outcomes [15].…”
Section: Introductionmentioning
confidence: 99%